Pengaruh Edukasi Kesehatan Reproduksi terhadap Pengetahuan pada Remaja Pubertas di SMPN 1 Kapala Pitu Tahun 2022: Influence of Reproductive Health Education on Knowledge of Adolescent Puberty at SMPN 1 Kapala Pitu, 2022 - Syamsuddin, Sri Devi (Jurnal Midwifery, 2023)
Introduction Health education is a process to improve people's ability to maintain and improve their health. Adolescent reproductive health is a healthy condition physically, mentally and socially related to the reproductive system, functions and processes possessed by adolescents. This study aims to determine the effect of reproductive health education on the level of knowledge of adolescents about reproductive health. Method This research was carried out at SMPN 1 Kapalan Pitu, Kab. Toraja. Sample 150 respondents. Purposive sampling technique does not provide equal opportunities for each population. Pre-experimental method with a one group pre-test post-test approach. The research instrument is a questionnaire. The data analysis technique used the one sample test. Result showed that Asyimp Sig (2 Sided) 0.000 (α<0.05) was obtained. It can be concluded that there is an effect of providing education about reproductive health on the knowledge of puberty adolescents. Conclusion is that there is a significant influence between the implementation of adolescent reproductive health education on the level of adolescent knowledge about reproductive health. For this reason, the researchers hope that this research can be used as a form of routine activity to broaden students' insights about the reproductive system.